Jual Beli Online dalam Perspektif Islam - Achmad Zurohman; Eka Rahayu (Fakultas Ekonomi dan Bisnis Islam, 2019)
Human life is inseparable from buying and selling activities. Along with the times, buying and selling is not only done in the real market but online using the internet. This study aims to analyze how Islam views online buying and selling. This study uses library research to provide a comprehensive explanation of the advantages and disadvantages of online buying and selling. Online buying and selling is a buying and selling activity that does not require sellers and buyers to come face to face. The buyer makes a payment frst then proceed with the delivery of the goods. The Taudhihul ahkammembagi divides the legal conditions of buying and selling into two, namely 1) the seller and the buyer must be willing and there is no element of compulsion, and 2) trade in sacred and benefcial goods. Through online sales, sellers and buyers get many benefts. Sellers do not need a lot of money for promotions, etc. Buyers can access goods anywhere without the limitations of time and place, provided they are connected to the internet. The disadvantage of buying and selling online is that it is prone to fraud if the buyer is not careful and careful. The buyer must be able to select and choose a store that can be trusted. Online buying and selling in Islam is also called greeting, where the buyer pays frst then the seller sends the goods. Muamalah is permissible in Islam as long as it is in harmony and the conditions.